Free alternatives to everyday software - Beecher, Karl (Apress, 2018)
"Explore the practical process of moving part or all of your software usage towards open source software (OSS). The material in this video is divided into two parts, each offering a different perspective - one general, one specific. The first part describes the general, practical considerations for a user who moves to OSS alternatives. The considerations include: obtaining the software, migrating your data, getting support and training, and arranging for ongoing support and maintenance. For each consideration, Free Alternatives to Everyday Software gives advice on how best to approach the task and any risks to watch out for. The second part discusses prominent examples of OSS in a number of key categories (office software, browsers, email, and so on). Each segment identifies an OSS program and explains the challenges you will face when moving to that program (for example, 'Where is feature X in the OSS version?', 'Will there be issue with driver support?', and so on)."--Resource description page